Listeria monocytogenes Infections in Hematopoietic Cell Transplantation Recipients: Clinical Manifestations and Risk Factors. A Multinational Retrospective Case-Control Study from the Infectious Diseases Working Party of the European Society for Blood and Marrow Transplantation - Averbuch, Dina; Tridello, Gloria; Wendel, Lotus; Itälä-Remes, Maija; Oren, Ilana; Karas, Michal; Blijlevens, Nicole; Beguin, Yves; Broers, Annoek; Calore, Elisabetta; Cattaneo, Chiara; Isaksson, Cecilia; et al. (Transplantation and cellular therapy, 2024)
Listeriosis is rare after hematopoietic stem cell transplantation (HCT). Little is known about listeriosis in this population. In this retrospective international case-control study, we evaluated 41 listeriosis episodes occurring between 2000 and 2021 in HCT recipients (111 transplant centers in 30 countries) and assessed risk factors for listeriosis by comparisons with matched controls. The 41 listeriosis episodes (all due to Listeria monocytogenes [LM]) occurred in 30 allogeneic (allo)-HCT recipients and 11 autologous (auto)-HCT recipients at a median of 6.2 months (interquartile range [IQR], 1.6 to 19.3 months) post-HCT. The estimated incidence was 49.8/100,000 allo-HCT recipients and 13.7/100,000 auto-HCT recipients. The most common manifestations in our cohort were fever (n = 39; 95%), headache (n = 9; 22%), diarrhea, and impaired consciousness (n = 8 each; 20%). Four patients (10%) presented with septic shock, and 19 of 38 (50%) were severely lymphocytopenic. Thirty-seven patients (90%) had LM bacteremia. Eleven patients (27%) had neurolisteriosis, of whom 4 presented with nonspecific signs and 5 had normal brain imaging findings. Cerebrospinal fluid analysis revealed high protein and pleocytosis (mainly neutrophilic). Three-month mortality was 17% overall (n = 7), including 27% (n = 3 of 11) in patients with neurolisteriosis and 13% (n = 4 of 30) in those without neurolisteriosis. In the multivariate analysis comparing cases with 74 controls, non-first HCT (odds ratio [OR], 5.84; 95% confidence interval [CI], 1.10 to 30.82; P = .038); and lymphocytopenia <500 cells/mm3 (OR, 7.54; 95% CI, 1.50 to 37.83; P = .014) were significantly associated with listeriosis. There were no statistically significant differences in background characteristics, immunosuppression, and cotrimoxazole prophylaxis between cases and controls. HCT recipients are at increased risk for listeriosis compared to the general population. Listeriosis cause severe disease with septic shock and mortality. Neurolisteriosis can present with nonspecific signs and normal imaging. Lymphocytopenia and non-first HCT are associated with an increased risk of listeriosis, and cotrimoxazole was not protective.
Keywords: senioři; Retrospective Studies; Incidence; Listeriosis; Europe; Listeria monocytogenes; Evropa; Middle Aged; mužské pohlaví; studie případů a kontrol; incidence; Adult; Hematopoietic Stem Cell Transplantation; listeriové infekce; ženské pohlaví; transplantace hematopoetických kmenových buněk; retrospektivní studie; Humans; lidé středního věku; rizikové faktory; Case-Control Studies; dospělí; Female; Risk Factors; Aged; lidé; Male